FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KB PASCA SALIN PADA IBU NIFAS DI WILAYAH KERJA PUSKESMAS PAKUAN BARU KOTA JAMBI TAHUN 2013 - Ruwayda Ruwayda (Universitas Batanghari Jambi, 2014)
Family Planning on Post partum women are very supportive of health development goals and this is also supported by a number of prospective new planning participants (pregnant women and maternity) that have been in contact with health professionals . One health center care with delivery that is high enough Pakuan Baru health center but the achievement of the post- partum family planning participants still showed a low number, from 689 deliveries as the participants of family planning post partum women is 382 mothers (55.44%)This study is a descriptive cross-sectional design that aims to see the picture and the relationship of knowledge , attitude , family support , the role of the family planning officials in the family planning on post- partum Pakuan Baru primary health care Year 2013. The study was conducted in August of 2013 , The research is in the BPM ( midwife Independent Practice ) and in pakuan baru primary health care. The study population was all women giving birth in health centers and in Pakuan Baru totaled 689 mother , the sample in this study, the entire maternity August - September 2013 (followed by 42 days ) by 67 mothers .The results of the study most of the respondents are less well using post- partum family planning was 53 ( 60.9 %) , most of the poor knowledge of 64 ( 73.6 % ) , poor attitude was 68 ( 78.2 % ) , lack of family support either 62 ( 71.3 % ) , role of officers good health 54 (62.1 %) . There is a relationship of knowledge, attitudes, role of officers , family support with post partum family planning in pakuan baru primary health care year 2013Advice to the Department of Health to make policy for health centers including Midwives Independent Practice (BPM) in an effort to increase the post-partum family planning provides leaflets , brochures , as a medium of information to the public, especially improving maternal knowledge . In order to provide the BPPKB , through field officers PLKB do counseling , motivating maternal post partum immediately after use family planning . Health center mini workshop meeting, committed midwife in order to introduce family planning post partum and conduct training midwives practice independently` . Keywords : KB post- partum , knowledge , attitude , family support , role of officers